Performance Analysis of Cloud Computing Simulator CloudSim with Virtual Machine Configuration Changes - giriwahyuwiriasto; M. Fajar Wirayudha; Ahmad Satriadi (Depertment of Electrical Engineering University of Mataram, 2024)
In the era of digital transformation, cloud computing simulation plays a crucial role in understanding and optimizing system performance before implementation. This research focuses on the performance analysis of CloudSim simulation by varying virtual machine (VM) parameters. The altered parameters include processor speed (MIPS), RAM size, and the number of CPUs. The research objective is to comprehend the impact of these changes on overall cloud system performance. Experimental methods involve CloudSim initialization, datacenter, and broker creation, along with VM and cloudlet configuration. Simulation results are analyzed to unveil the relationship between VM parameters and cloudlet execution time. This study aims to provide practical guidelines for optimizing VM configurations in the cloud environment, enhancing system efficiency and responsiveness. The research findings have implications for the development of more adaptive and effective cloud systems in the future, serving as a foundation for further advancements in the field.